Metabolomics of Multimorbidity: Could It Be the Quo Vadis? - Dash, Pujarini; Mohapatra, Soumya R.; Pati, Sanghamitra (Frontiers in Molecular Biosciences, 2022)
Multimorbidity, the simultaneous presence of two or more chronic diseases, affects the health care to a great extent. It’s association with health care cost, more disability and poor quality of life, makes it a major public health risk. The matter of worry is that, management of multimorbid condition is complicated by the fact that multiple types of treatment may be required to treat different diseases at a time and the interaction between some of the therapies can be detrimental. Understanding the causal factors of simultaneously occurring disease conditions and investigating the connected pathways involved in the whole process may resolve the complication. When different disease conditions present in an individual share common responsible factors, treatment strategies targeting at those common causes will certainly reduce the chance of development of multimorbidity occurring because of those factors. Metabolomics that can dig out the underlying metabolites/molecules of a medical condition, is believed to be an effective technique for identification of biomarkers and intervention of effective treatment strategies for multiple diseases. We hypothesize that, understanding the metabolic profile may shed light on targeting the common culprit for different/similar chronic diseases ultimately making the treatment strategy more effective with a combinatorial effect.